2021
DOI: 10.1029/2021gl095041
|View full text |Cite
|
Sign up to set email alerts
|

Robust Evaluation of ENSO in Climate Models: How Many Ensemble Members Are Needed?

Abstract: ENSO generates large-scale sea surface temperature (SST) variations in the eastern equatorial Pacific Ocean, with SST anomalies typically between 1°C and 3°C, accompanied by changes in the oceanic thermal structure and currents, and in the atmospheric circulation and convective activity. General circulation models (GCMs) have striven to capture key observed characteristics of ENSO as documented by many previous studies (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…While the purpose of this study is to provide a detailed overview of ENSO projections in all available SMILEs, it is useful to provide some observational context. We note that a detailed comparison of ENSO characteristics in both CMIP models and SMILEs can be found in the following studies for a large range of ENSO metrics, and we do not repeat this here (Planton et al, 2021;Lee et al, 2021). We do, however, compare model-simulated and observed El Niño and La Niña composites (Figure S1 & S2).…”
Section: Datasetsmentioning
confidence: 97%
“…While the purpose of this study is to provide a detailed overview of ENSO projections in all available SMILEs, it is useful to provide some observational context. We note that a detailed comparison of ENSO characteristics in both CMIP models and SMILEs can be found in the following studies for a large range of ENSO metrics, and we do not repeat this here (Planton et al, 2021;Lee et al, 2021). We do, however, compare model-simulated and observed El Niño and La Niña composites (Figure S1 & S2).…”
Section: Datasetsmentioning
confidence: 97%
“…Additionally, a recent study by Lee et al. (2021) has suggested that large (≥50) ensembles are needed to robustly capture the baseline ENSO characteristics and physical processes. Given the large uncertainties in the IPCC AR5 model projections of ENSO intensity and the need of large ensembles, it would be important to apply the current framework to the state‐of‐art IPCC AR6 model large ensemble simulations to further tackle this scientific question.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Other wave-coupled effects, such as the effect of surface wave Stokes drift on air-sea momentum and heat fluxes, the effect of sea spray from wave breaking on air-sea heat fluxes, and the effect of SST diurnal cycle on air-sea heat and gas fluxes,-were also introduced to the climate models. Lee et al (2021) comprehensively evaluated all 59 CMIP6 climate models on their performance in reconstructing historical ENSO events, and FIO-ESM v2.0 ranked No. 1 among them (from their Figure S1).…”
Section: Ocean-to-climate Model Development and Applicationsmentioning
confidence: 99%
“…Lee et al. (2021) comprehensively evaluated all 59 CMIP6 climate models on their performance in reconstructing historical ENSO events, and FIO‐ESM v2.0 ranked No. 1 among them (from their Figure S1).…”
Section: Ocean‐to‐climate Model Development and Applicationsmentioning
confidence: 99%